(untitled) (DAPesquisa, 2020)
The design belongs to the field of applied social sciences and, therefore, accepts contributions from several areas to compose the graduation programmes. This, however, often contributes to the fragmentation of knowledge in the teaching of design, under the very usual name of interdisciplinarity. Today, design colleges in Brazil try to establish themselves as knowledge producers, but still focus on "teaching to do." This is what happens in disciplines of projectual practice, often without a theoretical-scientific base and, mainly, distant from the real user and the social reality surrounding the university. The objectives of higher education and its duties towards society, as determined by specific laws, such as the Law of Directives and Bases of National Education - Law Number 9,394/1996, are ignored. Based on these questions and with a focus on ethics in higher education in design, this article was constructed using the literature review and the description of a classroom experience, with the objective of questioning and evaluating the teaching practice in a faculty of design and the role of the design teacher in the teaching-learning processes. It was concluded that these processes represents a complex reality and that studies in this area deserve unfolding